Response of Summer Maize Photosynthate Accumulation and Distribution to Shading Stress Assessed by Using 13CO2 Stable Isotope Tracer in the Field - Gao, Jia; Zhao, Bin; Dong, Shuting; Liu, Peng; Ren, Baizhao; Zhang, Jiwang (Frontiers in Plant Science, 2017)
Maize is one of the most important crops globally that provides food, feed, and bioenergy. However, shading stress threatens maize production. In this study, we investigated the effects of shading on photosynthate accumulation and distribution of summer maize in the field. Zhengdan958 (ZD958) and Denghai 605 (DH605) were used as experimental materials in a field experiment running from 2013 to 2015. Shading treatments were applied over different growth stages: from the tassel stage (VT) to physiological maturity (R6) (S1), from the six-leaf stage (V6) to VT (S2), and from emergence stage (VE) to R6 (S3). The effects of shading on plant photosynthesis, photosynthate accumulation and distribution, and yield were evaluated in comparison to ambient sunlight. Shading significantly decreased the leaf area, SPAD value, net photosynthetic rate, dry matter accumulation, and grain yield. During the 3-year experimental period, grain yields of ZD958 and DH605 were reduced by 83.4%, 34.2%, 53.1% and 79.3%, 24.2%, 57.6% as compared to the CK by treatments S3, S2, and S1, respectively. 13CO2 stable isotope tracing revealed that shading differentially affected the photosynthate transfer rate in different stages; photosynthates were transferred from top to bottom plant parts, in the order control > S2 > S1 > S3. We conclude that shading clearly disrupted photosynthate metabolism, and reduced the photosynthate accumulation in the grain, resulting in a yield reduction.